Astrometric And Photometric Studies For Some Selected Open Star Clusters - Hariry, R. M.; Haroon, A.A.; Malawi, A. A.
In this study, we conducted a detailed astrometric, and photometric study of four open clusters (SAI 43, SAI 47, SAI 63, and SAI 113) using data from Gaia DR3. The ASteCA code enabled the identification of the astrometric and photometric parameters. The new centers of these clusters were redetermined and from Radial Density Profile (RDP), the cluster radii, are between 3.13- and 6.6 arcmin for all clusters. The astrophysical parameters are as follows: the number of star members N are 141 (SAI 43), 153 (SAI 47), 198 (SAI 63), and 188 (SAI 113); parallax (  ) for SAI 43, SAI 47, SAI 63, and SAI 113 are between 0.275 and 0.506 mas; proper motion parameters (  cos a ,   ) are (0.57, -0.54 mas/yr), (0, -0.34 mas/yr), (-0.24, 0.26 mas/yr), and (-5.61, 2.84 mas/yr) for SAI 43, SAI 47, SAI 63, and SAI 113, respectively. The photometric parameters include the color magnitude diagram (CMD), ages, reddening, and distances. The ages are provided as log (age), and they are between (7.172-8.659); the color excess E(B-V) is 0.476±0.017 mag for SAI 43, 0.375±0.014 mag for SAI 47, 0.510±0.009 mag for SAI 63, and 1.265±0.011 mag for SAI 113, the distance modules of the clusters are between 11.177-13.439 mag, and the distances from the sun to each of the clusters (SAI 43, SAI 47, SAI 63, and SAI 113) are calculated as 4900±100 pc, 2360±30 pc, 1720±20 pc, and 3720±50 pc, respectively.
Keywords: Astrophysics